Burnout syndrome or burning at work: a conflict in the professionals' health - Aranda, Carolina (2011)
Several risk factors derived from both the means of production and modes of organization can affect the health of workers or even death. Just one of the demonstrations in health is called burnout syndrome, which is considered as an advanced stage of work stress after being exposed continuously to the risk factor. Identification, evaluation and control are essential for adequate job performance. The burnout syndrome is a disease that disrupts the quality of family life, social and labor of whom suffers from it.